Increased circulating Th22 cells in patients with acute gouty arthritis: A CONSORT-compliant article. Issue 42 (October 2017) - Luo, Guangcheng; Yi, Tingting; Zhang, Guoyuan; Guo, Xiaolan; Jiang, Xingliang
Abstract: Background: T-helper 22 (Th22) cells are involved in host immunity against pathogen invasion and have been implicated in the pathogenesis of inflammatory diseases. However, the roles of Th22 cells in acute gouty arthritis remain unclear. Methods: A case–control study was employed to illustrate the clinical significance of Th22 cells in acute gouty arthritis. In this study, 27 patients with acute gouty arthritis, 22 patients with intercritical gout (IG), and 20 healthy controls were recruited, and peripheral blood cells and plasma were collected for the detection of Th22, Th17, and Th1 cells, and plasma interleukin (IL)-22. Results: The relative and absolute numbers of Th22 and Th17 cells were significantly higher in patients with acute gouty arthritis than in patients with IG and healthy controls. Plasma IL-22 levels were consistently higher in patients with acute gouty arthritis than in patients with IG and healthy controls ( P  < .05). Th22 cell numbers were positively correlated with Th1 ( r  = 0.648, P  < .05) and Th17 ( r  = 0.379, P  < .05) cell numbers in patients with gout. Moreover, Th22 cell numbers and plasma IL-22 levels were positively correlated with C-reactive protein levels (Th22: r  = 0.444, P  < .05; IL-22: r  = 0.282, P  < .05). Conclusion: Our results indicate that peripheral blood levels of Th22 cells increase during acute gouty arthritis suggesting a role for these cells in the pathophysiology of the disease.